(untitled) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
This study aims to examine sexual repression and obsession in Vladimir Nabokov’s novel Nabokov & Boyd (1996) by Vladimir Nabokov, focusing on how psychological mechanisms shape the novel’s central conflict, as well as Humbert’s behavior, which views repression and obsession as normal personality traits. This study analyzes the underlying forces of both repression and obsession and their influence on the way Humbert interprets reality, makes decisions, and interacts with others. This study employs a descriptive qualitative method, focusing on the analysis of non-numerical data in the form of narrative text with the aim of generating interpretive insights. The analysis utilizes Freud’s psychoanalytic framework, which is based on the concepts of the Id, Ego, and Superego, as well as repression and defense mechanisms. The findings of this study highlight three main points. First is the formation of the concept of “nymphlet,” which functions as a fantasy object constructed from past trauma related to the death of Ammabel Leigh. Second is the pedophilic desire that is continuously sustained by the Id’s impulses—unresolved and repeatedly overpowering his rationality and morality. Third, the unresolved conflict between the unconscious desires Humbert creates and existing social norms in public; instead, the ego manages this tension by rationalizing it, thereby perpetuating the conflict. Therefore, this psychological process demonstrates how obsession distorts Humbert’s perception of reality, enabling him to continuously justify his actions and engage in behavior that violates moral standards. This study concludes that the Freudian psychoanalytic framework is an effective way to interpret “Lolita”; thus, this study argues that obsession and repression are the underlying forces that create conflict in the novel.